Prevention of Teratogenesis in Pregnancies of Obese Rats by Vitamin E Supplementation - Martin Alcala; Victoria E. Bolado; Isabel Sánchez-Vera; Sonia Clapés; Francisco Dasí; Guillermo Sáez; Esther Carrera; Fabiola Alvarez-Gallego; Mary R. Loeken; Marta Viana (MDPI AG, 2021)
Congenital malformations are a common adverse outcome in pregnancies complicated by pregestational obesity, although the underlying mechanisms are still unrevealed. Our aim was to study the effect of oxidative stress in obesity-induced teratogenesis. Wistar rats were fed a high-fat diet for 13 weeks, with (OE group) or without (O group) vitamin E supplementation. Then, rats were mated and sacrificed at day 11.5 of gestation. Embryos from O dams presented a 25.9 ± 3.5% rate of malformations (vs. 8.7 ± 3.4% in C rats), which was reduced in the OE group (11.5 ± 2.3%). Pregestational obesity induced hepatic protein and DNA oxidation and a decline in antioxidant enzymes. Importantly, glutathione content was also decreased, limiting the availability of this antioxidant in the embryos. Vitamin E supplementation efficiently maintained glutathione levels in the obese mothers, which could be used in their embryos to prevent oxidation-induced malformations. To test the effect of decreasing glutathione levels alone in a cell culture model of neuroepithelium, murine embryonic stem cells (ESC) were induced to form neuronal precursors and glutathione synthesis was inhibited with the gamma-glutamylcysteine synthesis inhibitor, buthionine sulfoximine (BSO). BSO inhibited the expression of Pax3, a gene required for neural tube closure that is also inhibited by oxidative stress. Taken together, our data indicate that obesity causes malformations through the depletion of maternal glutathione, thereby decreasing glutathione-dependent free radical scavenging in embryos, which can be prevented by vitamin E supplementation.